PENGARUH KEMAMPUAN PERSONAL, KECANGGIHAN TEKNOLOGI INFORMASI, DAN DUKUNGAN MANAJEMEN TERHADAP KINERJA SISTEM INFORMASI AKUNTANSI (Studi Empiris Pada Perusahaan BUMN Bidang Jasa Konstruksi di Kota Manado) - Senduk, Lidia; Karamoy, Herman; Kalangi, Lintje (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2021)
Accounting Information System (AIS) can provide financial information that companies need in making decisions. For this reason, a company needs an SIA that has good performance so that SIA that has good performance so that SIA can provide the information needed by the company quickly, accurately, consistently and reliably so that the decisions taken by the company are right. This study aims to analyze and prove empirically the influence of personal ability, sophistication of information technology, and management support on the performance of accounting information systems. This type of research is quantitative research, using primary data through questionnaires. Respondents in this study were all employees of BUMN in the field of construction services in Manado City. The population used is the accounting and finance department employees as many as 90 employees while the sample used is the entire population as a sample of 90 respondents. The data were analyzed using multiple linear regression analysis and data testing was carried out with the help of the SPSS version 22 program. The results of the study show that : 1). Personal ability has a positive effect on the performance of accounting information systems. 2). The sophistication of information technology has a positive effect on the performance of accounting information systems. 3). Management support has a positive effect on the performance of accounting information systems. The value of the determinant coefficient is 0,589. This shows that the magnitude of the influence of the independent variables, namely personal abilities, sophistication of information technology, and management support on the dependent variable, namely the performance of accounting information systems explained by the equation model in this study is 58,90%. While the remaining 41,10% is esplained by other factors outside this research model.